A field study of indoor air quality in a tropical refectory / Qi Jie Kwong, Farah Yasmin Sulaiman and Mohamad Sufian Hasim - Qi, Jie Kwong; Sulaiman, Farah Yasmin; Hasim, Mohamad Sufian (Faculty of Architecture, Planning and Surveying, 2016)
A refectory is the building area in educational institutions where meals and beverages are served. Since these areas are often occupied by a large number of students and staff during mealtime, the provision of good indoor air quality (IAQ) is of utmost importance. To supplement the available information about conditions of indoor air in many building areas which have been reported in other studies and to identify the levels of indoor air parameters (IAPs) in a Malaysian refectory, a field study has been carried out in a local university using electronic environmental monitoring sensors and questionnaire survey and the results are reported in this paper. The mean air temperature and concentration level of the carbon dioxide gas were found to be higher than the acceptable ranges stipulated in both DOSH and ASHRAE IAQ standards, while other IAPs were generally within the recommended levels. The split air-conditioning units, albeit installed near the dining zones of the refectory, were found to be inefficient at removing the occupant heat gain during peak hours and provided very limited ventilation effectiveness since there is no fresh air intake for this type of air conditioner. High prevalence of sick building syndrome (SBS) was also found in this building area, possibly due to the high occupancy levels. Increased ventilation with the aid of exhaust fans and retrofitting of the existing air conditioning system to a centralised one were required to lower the CO2 level as well as removing other airborne contaminants.